After successful fundraising: how overfunding and category spanning affect the release and audience-perceived quality of crowdfunded products - Clarissa E. Weber; Norbert Steigenberger; Hendrik Wilhelm (Small Business Economics, 2023)
Overfunding of crowdfunded product-development projects would seem to be a welcome outcome for entrepreneurs, yet initial theory and evidence suggest that overfunding can have both positive and negative consequences. To overcome these contradictory predictions, we develop theory linking research on slack resources, audience expectations, and product category spanning to hypothesize boundary conditions for whether and when overfunding has a positive or negative effect on the product-development outcomes of product release and audience-perceived product quality. Post-crowdfunding data on video-game development projects show that entrepreneurs with high-category-spanning products benefit substantially less from overfunding than entrepreneurs with low-category-spanning products. Our study provides novel insights into the relation between overfunding and product release as well as audience-perceived product quality. It also contributes to our emerging understanding of the role of categories in the context of crowdfunding. We discuss implications for theory and practice.
Keywords: L26; O31; G23; 330; Crowdfunding; Overfunding; Category spanning; Product release; Product quality